Statistical Validation of Surfaced Submarine Seakeeping Simulations Based on Open Water Tests - Büsken, Wiebke; Krüger, Stefan (American Society of Mechanical Engineers, 2024)
Submarines are frequently required to operate in surfaced condition, partially in harsh seaways. Since diving is not always possible or permitted, an accurate prediction of a submarine’s seakeeping performance at the surface becomes essential for safe operation. The seakeeping of a surfaced submarine is a complicated problem of motions in all six degrees of freedom, which strongly depends on the respective parameter combination of seaway, forward speed, encounter angle, and surface stability. In this paper, time-domain seakeeping simulations are performed for a modern submarine hull form in short-crested irregular waves using the potential flow theory-based computation method E4-ROLLS. The simulation results of the roll, pitch and heave motions are compared with data obtained from open water model tests. These model tests were recently performed on a bay in Germany using free-running submarine models and specifically focused on the surface stability’s influence on the seakeeping in natural seaways. The presented research contributed to the development of a novel surface stability regulation DMS 1030-2 for submarines of the German Navy.